Developmental Aspects of Initial sC Clusters in Croatian Children - Mildner, Vesna; Tomić, Diana (2011)
The aim of the study was to analyze the acquisition of nine initial sC clusters /sp-, st-, sk-, sm-, sn-, sl-, sr-, sv-, sj-/ in typically developing Croatian children. Data collection included 30 participants (15 boys and 15 girls) aged between 26 and 48 months (mean: 38 months) in a picture naming task. The results were analyzed for percentage of correct responses and patterns of errors. As a group, /s/+NASAL clusters were produced most correctly (71%), followed by /s/+STOP (66%) with cluster reduction to the second member as the most frequent error. Retention of the first member, i.e. /s/, was the most frequent error in /s/+APPROXIMANT clusters (sv-/, /sj-/ and /sl-/, with the average of 57% correct responses across the three clusters. The most difficult was the /sr-/ cluster (24% correct), with substitution of /r/ with another sound being the most frequent error.
Projekt MZOS
ENG